Heat shock protein 70/alpha-fetoprotein epitope peptide induced specific immunity against hepatocarcinoma. Issue 5 (April 2019) - Xu, Bing; Wang, Xiaoping; Ma, Xiaojun; Lin, Huanping
Abstract: To study anti-tumor immunity mechanism induced by a reconstructed peptide complex-heat shock protein 70 (HSP70) and alphafetop-rotein (AFP), Mic e were immunized with AFP peptide, HSP70 and HSP70-AFP peptide complex es respectively. The killing effects of IFN-γ, TNF-α, perforin, granzyme B and CD8 + T cells on H22 cells were detected in each group of CD8 + T cell culture supernatants and investigate theimmune effect of heat shock protein 70 (HSP70)-alpha-fetoprotein (AFP)epitope peptide complex on mouse H22 hepatoma cells.